Electrochemical detection of single E. coli bacteria labeled with silver nanoparticles1. (19th June 2015) - Sepunaru, Lior; Tschulik, Kristina; Batchelor-McAuley, Christopher; Gavish, Rachel; Compton, Richard G.
<x xml:space="preserve">Abstract</x> A proof of concept for the electrochemical detection of single Escherichia coli bacteria decorated with silver nanoparticles is demonstrated.